2006
DOI: 10.1523/jneurosci.1073-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Hand Input to Area 3b Revealed by Converging Hemodynamic and Electrophysiological Analyses in Macaque Monkeys

Abstract: Functional magnetic resonance imaging (fMRI) of the hand representation in primary somatosensory cortex (area 3b) of macaque monkeys revealed an ipsilateral hand input undetected by most previous studies. Ipsilateral responses had a hemodynamic signature indistinguishable from that of contralateral hand responses. We explored the neural mechanisms of the fMRI effects using a second derivative analysis of field potentials [current source density (CSD) analysis] combined with action potential profiles, sampled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 48 publications
8
78
1
Order By: Relevance
“…Increases in blood flow in monkey visual cortex were not accompanied by increases in neuronal spiking activity during the period that the monkey was anticipating the onset of the actual trial (22) and decreases in BOLD responses in monkey visual cortex were not accompanied by changes in either spiking activity or high-frequency LFP power during perceptual suppression (23). Increased BOLD response in monkey SI after electrical stimulation of the median nerve was interpreted to reflect net local inhibition (14). In this study, the ipsilateral SI inhibition, measured with current source density analysis, was suggested to be mediated by intrahemispheric feedback inputs and not by transcallosal connections, demonstrating that increases in fMRI responses can reflect net inhibition in the intact cortex.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Increases in blood flow in monkey visual cortex were not accompanied by increases in neuronal spiking activity during the period that the monkey was anticipating the onset of the actual trial (22) and decreases in BOLD responses in monkey visual cortex were not accompanied by changes in either spiking activity or high-frequency LFP power during perceptual suppression (23). Increased BOLD response in monkey SI after electrical stimulation of the median nerve was interpreted to reflect net local inhibition (14). In this study, the ipsilateral SI inhibition, measured with current source density analysis, was suggested to be mediated by intrahemispheric feedback inputs and not by transcallosal connections, demonstrating that increases in fMRI responses can reflect net inhibition in the intact cortex.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in addition to pyramidal neurons and glial cells releasing vasodilators, increases in inhibitory interneuron activity can enhance blood flow in the cerebellum (11) and induce vessel vasodilation (12,13). Furthermore, increased BOLD responses in monkey SI have been attributed to net local inhibition (14). Thus, it is unclear how the fMRI responses observed in inappropriate cortical areas of human patients and rodents should be interpreted after plasticity following recovery from central or peripheral nerve injury.…”
mentioning
confidence: 99%
“…2C). Activity in L4 is modeled to reflect drive from the thalamus and was based on several studies of intracranial laminar electrophysiological recordings of evoked responses in SI, including responses to vibrissa and thalamic stimuli in rodents (Di et al, 1990;Barth and Di, 1991;Castro-Alamancos and Connors, 1996;Kandel and Buzsáki, 1997;Douglas and Martin, 2004), trigeminal stimulation in piglets (Ikeda et al, 2005), and tactile (Kulics and Cauller, 1986;Cauller and Kulics, 1991) and median nerve stimuli in awake monkeys (Peterson et al, 1995;Lipton et al, 2006). A second source of drive to the SI network contacted the distal apical dendrites in the supragranular layers of each neuronal population (Fig.…”
Section: Computational Neural Modelmentioning
confidence: 99%
“…Additionally, imaging and neurophysiological studies (in monkeys, Iwamura et al, 2001;Lipton et al, 2006;in humans, Allison et al, 1989a,b;Korvenoja et al, 1995;Nihashi et al, 2005;Hlushchuk et al, 2006) described modifications of SI (area 3b) activity in response to input evoked by either mechanical stimulation of an ipsilateral skin site or electrical stimulation of an ipsilateral peripheral nerve. Human investigations have shown that ipsilateral input can modify the SI response to a subsequent contralateral stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Schnitzler et al (1995), using magnetoencephalography (MEG), reported that concurrent tactile stimulation of the ipsilateral hand enhances the response of SI to stimulation of the contralateral median nerve. Conversely, (1) Korvenoja et al (1995) reported that the SI activation (detected using MEG) evoked by contralateral median nerve stimulation is suppressed during ipsilateral hand movement, (2) functional magnetic resonance imaging studies in both monkeys (Lipton et al, 2006) and humans (Hlushchuk et al, 2006) showed that an ipsilateral skin stimulus evokes CNS actions that partially suppress the SI response to a contralateral stimulus, (3) destruction of SI in one hemisphere (rats) was shown to be accompanied by the appearance (in the opposite SI) of neurons with bilateral receptive fields [interpreted to indicate that SI activity exerts a suppressive influence on SI neurons in the opposite hemisphere (Pluto et al, 2005)], and (4) low-frequency transcranial magnetic stimulation of sensorimotor cortex (in humans, Pal et al, 2005) was found to reduce excitability in the opposite hemisphere. Viewed collectively, these findings raise the possibility that the response of the SI hand region to a tactile stimulus (and thus the stimulus-evoked perceptual experience) may be subject to modulatory influences arising from the ipsilateral hand.…”
Section: Introductionmentioning
confidence: 99%